Terms of trade and economic growth in Argentina - Artana, Daniel (2011)
We define the terms of trade (of both goods and services) as an index of Price of Imports (PM) divided by the Index of Export Prices (PX). Then, following the usual approach, foreign trade is a sort of technology in which inputs of the country are exports (X) and products are imports (M). Inputs are processed into products at a rate determined by the relationship between the price of exports and imports, which is the inverse of the terms of trade. From such a point of view, declining terms of trade, as experienced by Argentina in recent years, act exactly as a technological shock, since a given quantity of exports can produce a greater volume of imports. Becker and Mauro (2005) have computed for a sample of several countries that the costlier shocks correspond to the terms of trade. Easterly and others (1993) express that "shocks, especially those to terms of trade, play a large role in explaining the variance in growth," thereby contributing to its unstable character. There is some evidence that the correlation between changes in the terms of trade and real GDP is significant. Kehoe and Ruhl (2007), for example, have pointed that this number ranges between -0.30 for the U.S. and -0.73 for Mexico. It seems that the correlation with changes in the TFP has been even stronger (amounting to -0.54 and -0.71, respectively). However, the same authors have stressed that this effect is not a first order effect when the product is measured as a chained index, because if the GDP is measured using a fixed base year (as in Argentina) the effects are ambiguous, even when they may have an impact on consumption and welfare. Kehoe and Ruhl identify here a puzzle: the increase in the terms of trade is frequently accompanied by declines in productivity, so that, “If there is a causal mechanism that links shocks to the terms of trade to movements in productivity, researchers need to identify it.” In this article we will measure the magnitude of the potential gains associated with the decrease in the terms of trade in terms of productivity, and seek to find a theory compatible with the observed facts that could be used to explain a first-order effect on GDP measured, as in Argentina, according to a fixed basket of goods and services.